2010
DOI: 10.1128/jvi.01428-09
|View full text |Cite|
|
Sign up to set email alerts
|

Conserved Residues in the UL24 Protein of Herpes Simplex Virus 1 Are Important for Dispersal of the Nucleolar Protein Nucleolin

Abstract: The UL24 family of proteins is widely conserved among herpesviruses. We demonstrated previously that UL24 of herpes simplex virus 1 (HSV-1) is important for the dispersal of nucleolin from nucleolar foci throughout the nuclei of infected cells. Furthermore, the N-terminal portion of UL24 localizes to nuclei and can disperse nucleolin in the absence of any other viral proteins. In this study, we tested the hypothesis that highly conserved residues in UL24 are important for the ability of the protein to modify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…HHV-1 and HHV-8 DNA were available to us (b) The presence of at least one PQS in the regulatory region of the gene (c) Conserved functions across all human herpesviruses or genes with a well-established role in viral pathogenesis. The UL2 gene codes for uracil DNA-glycosidase [45], A DNA repair protein and the UL24 gene codes for a nucleolin transporter protein [46] ;essential for efficient viral replication. These two proteins are present in all human herpesviruses.…”
Section: Resultsmentioning
confidence: 99%
“…HHV-1 and HHV-8 DNA were available to us (b) The presence of at least one PQS in the regulatory region of the gene (c) Conserved functions across all human herpesviruses or genes with a well-established role in viral pathogenesis. The UL2 gene codes for uracil DNA-glycosidase [45], A DNA repair protein and the UL24 gene codes for a nucleolin transporter protein [46] ;essential for efficient viral replication. These two proteins are present in all human herpesviruses.…”
Section: Resultsmentioning
confidence: 99%
“…Lytic induction also caused redistribution of nucleolin; rather than being confined to a discrete dot, nucleolin within cells expressing ZEBRA was visibly dispersed. Dispersal of nucleolin also occurs during lytic infection of HSV-1 and is mediated by the UL24 protein (51,52). In cells transfected with Z(R183E), nucleolin was not recruited to aggresomes (supplemental Fig.…”
Section: Z(k178d) Z(r179e) Z(r183e) and Z(r190e) Mutants Are Partimentioning
confidence: 98%
“…This result indicates that this alteration of the nucleoli in HSV-1-infected cells is partially dependent on UL24 (Lymberopoulos et al 2011). The fact that deletion of UL24 conserved homology domains, including the putative endonuclease motifs, resulted in loss of nucleolin and B23 dispersal activity suggests that this function may be shared among all herpesviruses and must be relevant for the viral life cycle (Bertrand et al 2010;Bertrand and Pearson 2008;Lymberopoulos et al 2011). Indeed, a study with UL24 homologues from human herpesviruses representative of each subfamily (HSV-1 UL24, HCMV UL76, and KSHV ORF20) showed that all these genes are able to induce cell cycle arrest followed by apoptosis.…”
Section: Virus and Nuclear Structures Affecting Cell Cyclementioning
confidence: 91%
“…During infection with HSV-1, UL24 family gene homologues are detected predominantly in the nucleus and transiently localize in the nucleoli (Hong-Yan et al 2001;Nascimento and Parkhouse 2007;Pearson and Coen 2002;Wang et al 2000Wang et al , 2004. Expression of the N-terminal domain of UL24 is sufficient to induce the redistribution of nucleolin in the nucleus (Bertrand et al 2010;Bertrand and Pearson 2008). However, cells infected with two independent UL24-deficient viruses, UL24XB and UL24XG, retain the prominent foci of nucleolin staining, although the pattern was not identical to the uninfected cells.…”
Section: Virus and Nuclear Structures Affecting Cell Cyclementioning
confidence: 99%